2021
DOI: 10.1137/18m1209489
|View full text |Cite
|
Sign up to set email alerts
|

Parameterized Approximation Schemes for Steiner Trees with Small Number of Steiner Vertices

Abstract: We study the Steiner Tree problem, in which a set of terminal vertices needs to be connected in the cheapest possible way in an edge-weighted graph. This problem has been extensively studied from the viewpoint of approximation and also parametrization. In particular, on one hand Steiner Tree is known to be APX-hard, and W[2]-hard on the other, if parameterized by the number of non-terminals (Steiner vertices) in the optimum solution. In contrast to this we give an efficient parameterized approximation scheme (… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…For the parameterization by the number of Steiner vertices in the optimum solution, a folklore result says that Steiner Tree is W [2]-hard (cf. [22,28]). However a parameterized approximation scheme exists for this parameter [28].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For the parameterization by the number of Steiner vertices in the optimum solution, a folklore result says that Steiner Tree is W [2]-hard (cf. [22,28]). However a parameterized approximation scheme exists for this parameter [28].…”
Section: Introductionmentioning
confidence: 99%
“…[22,28]). However a parameterized approximation scheme exists for this parameter [28]. Similar results have been found for special cases of DSN [19].…”
Section: Introductionmentioning
confidence: 99%
“…Dvorák et.al. [10] gave an efficient parameterized approximation scheme, parameterized by the number of terminals, for constructing a Steiner tree on an undirected weighted graph, and claim that such a scheme is unlikely to exist for directed graphs for the same parameter.…”
Section: Introductionmentioning
confidence: 99%
“…In their pioneering work Lokshtanov et al showed, inter alia, that various parameterized problems which do not 1 admit "classical" polynomial kernels have α-approximate kernels (also called "lossy kernels") of polynomial size. This line of work has attracted much attention, and finding lossy kernels of polynomial size, especially for problems which don't admit classical kernels of polynomial size, is an important-and challenging-area of current research in parameterized algorithms [13,8,7,9].…”
Section: Introductionmentioning
confidence: 99%